2014
DOI: 10.1038/ismej.2014.162
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial assembly and temporal dynamics in activated sludge of a full-scale municipal wastewater treatment plant

Abstract: Understanding environmental and biological influences on the dynamics of microbial communities has received great attention in microbial ecology. Here, utilizing large time-series 16S rRNA gene data, we show that in activated sludge of an environmentally important municipal wastewater treatment plant, 5-year temporal dynamics of bacterial community shows no significant seasonal succession, but is consistent with deterministic assemblage by taxonomic relatedness. Biological interactions are dominant drivers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
235
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 432 publications
(255 citation statements)
references
References 44 publications
19
235
0
1
Order By: Relevance
“…Ample experimental evidence has provided support for both stochastic and niche-based species-sorting processes in the assembly of bacterial communities in wastewater treatment facilities (4)(5)(6)(7)(8)(9). An early quantitative survey of bacteria in industrial activated sludge from our laboratory showed that the distribution of the most abundant bacteria fitted a geometric distribution, suggesting that resource competition was a primary factor determining the assembly characteristics of those populations (10).…”
mentioning
confidence: 99%
“…Ample experimental evidence has provided support for both stochastic and niche-based species-sorting processes in the assembly of bacterial communities in wastewater treatment facilities (4)(5)(6)(7)(8)(9). An early quantitative survey of bacteria in industrial activated sludge from our laboratory showed that the distribution of the most abundant bacteria fitted a geometric distribution, suggesting that resource competition was a primary factor determining the assembly characteristics of those populations (10).…”
mentioning
confidence: 99%
“…The trimmed paired-reads were merged by the PEAR program (version 0.9.5) [32] with a p-value of 0.01. On average, there were more than 30,000 raw sequences for each sample obtained for data analysis.…”
Section: Sequence Data Processing and Statistical Analysismentioning
confidence: 99%
“…Many ecological studies of full‐ and laboratory‐scale AS reactors showed that the microbial community temporally succeeds with no adverse effect on process performance (Wang et al ; Wells et al ; Valentín‐Vargas et al ; Ju and Zhang ). These results suggest that temporal change in community structure may be normal in AS reactors.…”
Section: Introductionmentioning
confidence: 99%